Three-dimensional dental arch changes of patients submitted to orthodontic-surgical treatment for correction of Class II malocclusion - Peixoto, Adriano Porto [UNESP]; Pinto, Ary Dos Santos [UNESP]; Garib, Daniela Gamba; Gonçalves, João Roberto [UNESP] (Dental Press International, 2014)
INTRODUCTION:This study assessed the three-dimensional changes in the dental arch of patients submitted to orthodontic-surgical treatment for correction of Class II malocclusions at three different periods.METHODS:Landmarks previously identified on upper and lower dental casts were digitized on a three-dimensional digitizer MicroScribe-3DX and stored in Excel worksheets in order to assess the width, length and depth of patient's dental arches.RESULTS:During orthodontic preparation, the maxillary and mandibular transverse dimensions measured at the premolar regions were increased and maintained throughout the follow-up period. Intercanine width was increased only in the upper arch during orthodontic preparation. Maxillary arch length was reduced during orthodontic finalization, only. Upper and lower arch depths were stable in the study periods. Differences between centroid and gingival changes suggested that upper and lower arch premolars buccaly proclined during the pre-surgical period.CONCLUSIONS:Maxillary and mandibular dental arches presented transverse expansion at premolar regions during preoperative orthodontic preparation, with a tendency towards buccal tipping. The transverse dimensions were not altered after surgery. No sagittal or vertical changes were observed during the follow-up periods.

Introdução: esse estudo avaliou as alterações tridimensionais ocorridas na morfologia das arcadas dentárias de pacientes submetidos ao tratamento ortodôntico-cirúrgico para a correção da má oclusão de Classe II, em três períodos distintos: (T1 ) modelos iniciais, (T2 ) modelos pré-cirúrgicos imediatos (de 1 a 15 dias antes da cirurgia) e (T3 ) modelos pós-cirúrgicos (mínimo de 6 meses após a remoção do aparelho ortodôntico). Métodos: pontos previamente demarcados em cada modelo foram digitalizados por meio do digitalizador tridimensional MicroScribe-3DX, cujas coordenadas, armazenadas em planilhas do programa Excel, deram origem a valores que possibilitaram a avaliação da largura, comprimento e profundidade das arcadas dentárias. Resultados: durante o preparo ortodôntico, houve aumentos nas distâncias transversais superiores e inferiores medidas na região de pré-molares que se mantiveram no período total de acompanhamento. Apenas a distância intercaninos superior apresentou alterações de aumento durante o preparo ortodôntico, assim como a largura da arcada superior, que diminuiu durante a fase de finalização. A profundidade de ambas as arcadas manteve-se estável nas fases avaliadas. Diferenças entre as mudanças dos pontos centroide e gengival sugerem que os pré-molares superiores e inferiores inclinaram para vestibular durante o preparo ortodôntico pré-cirúrgico. Conclusões: conclui-se que as arcadas dentárias superiores e inferiores sofreram expansão transversal na região de pré-molares durante o preparo ortodôntico pré-cirúrgico, com tendência à inclinação vestibular de todos os dentes posteriores. Após a cirurgia, as dimensões transversais não foram afetadas. Não foram observadas alterações sagitais ou verticais durante os períodos de observação.
Keywords: Orthodontics; Orthognathic surgery; Malocclusion; Dental models; Ortodontia; Cirurgia ortognática; Má oclusão; Modelos dentários